2003
DOI: 10.1097/00126334-200306010-00016
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Adherence to Antiviral Therapy in HIV-Infected Children Using the Medication Event Monitoring System, Pharmacy Refill, Provider Assessment, Caregiver Self-Report, and Appointment Keeping

Abstract: The authors sought to assess the utility of the electronic Medication Event Monitoring System (MEMS) in monitoring adherence to highly active antiretroviral therapy (HAART) in HIV-infected children and to compare this with other methods of adherence assessment. Twenty-six perinatally HIV-infected children being treated with three or more antiretroviral medications and their caregivers were enrolled and prospectively followed-up for 6 months. Adherence was assessed using MEMS monitoring of one antiretroviral, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
116
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(129 citation statements)
references
References 15 publications
10
116
0
3
Order By: Relevance
“…The active joint count finding contradicts pediatric studies that reported greater disease activity to be associated with lower adherence to medications for HIV (18), renal disease (23), and seizures (24). However, these studies were cross-sectional, and it is possible that lower adherence produced increased disease activity.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The active joint count finding contradicts pediatric studies that reported greater disease activity to be associated with lower adherence to medications for HIV (18), renal disease (23), and seizures (24). However, these studies were cross-sectional, and it is possible that lower adherence produced increased disease activity.…”
Section: Discussionmentioning
confidence: 64%
“…A recent study of children with human immunodeficiency virus (HIV) (18) also supports the 80% cutoff score. In this study children with detectable viral loads (a measure of active disease) were Ͻ80% adherent to highly active antiretroviral therapy (18).…”
Section: Discussionmentioning
confidence: 98%
“…In the 3 studies that assessed adherence by clinic attendance, estimates varied almost linearly according to the assessment interval, with lower levels for longer intervals. For example, perfect clinic attendance was achieved by 21% of the patients in the previous 365 days, 33 65% in the previous 180 days, 34 and 88% of patients in the previous 90 days. 31,33 As seen in Table 1, the 3 studies that used therapeutic drug monitoring, the 2 that relied on medical chart review, and the 2 with EDM generally produced lower estimates of adherence than did studies using the other methods.…”
Section: Estimates Of Adherence According To Assessment Methodsmentioning
confidence: 99%
“…Self-reported/caregiver adherence tends to overestimate the prevalence of adherence due to social desirability or recall bias factors [27]. In this sense, Farley et al found self-report to be unreliable when compared with electronic measurement [28].…”
Section: Assessing Adherence To Pediatric Cartmentioning
confidence: 99%